Diversity, floristic composition and structure of a Seasonally Dry Marañon Forest in the district of Utco, Celendin, Cajamarca, Peru. - Roncal-Rabanal, M.R. (2023)
Seasonally dry forests (BES) are permanently threatened by several anthropic and natural activities that have been reducing the environmental services they offer; In this sense and with the purpose of contributing to the ecological knowledge of this type of ecosystem, the vegetal characterization of a BES of the Marañon was carried out in the district of Utco, Celendin, Cajamarca, in the north of Peru. Three study zones were stratified every 300 m: from 850 to 1700 m asl; Sampling was carried out in the wet season using 30 modified Gentry transects of 50 x 2 m (0.1ha), considering a minimum distance between plots of 50 m; plant composition information was recorded; when the individuals presented a diameter greater than 1 cm, the DAP was taken and when it was less than 1 cm, its presence was recorded; the botanical collection followed the conventional technique, identifying the samples in the CPUN herbarium; the main diversity indices were evaluated and a Non-Metric Dimensional Scaling (NMDS) was performed with RStudio. 52 species and 7 taxa at the genus level distributed in 56 genera and 25 families of the Angiospermae subdivision were recorded; 31 bushy, 10 herbaceous, nine arboreal, six succulents and three climbers. The most diverse families were Fabaceae (11sp), Asteraceae (7sp) and Cactaceae (6sp). Fourteen endemic species from Peru and nine from BES Marañon are reported. Margalef diversity (DMg) and Simpson dominance (D) were high for Zone III; Sorensen (IS) and Jaccard (J) indices showed greater similarity between Zones I and II. The greatest abundance and relative frequency (AR - FR) was found by Cienfuegosia tripartita (42.30%, 9.2%); the highest basal area (BA) relative dominance (DR) and IVI, Eriotheca discolor (BA=629.8 m2/0.1ha, DR=84.7%, IVI=97.34). The elevational diametric distribution pattern is predominantly shrubby. Copyright © 2023 ICMPE.